Pengoptimalan Penggunaan Marketplace Dalam Kegiatan Pendampingan Sumber Daya Manusia Pada UMKM Sabun Cair di Tambun Selatan Bekasi - Fata Nidaul Khasanah; Dhian Tyas Untari; Timorora Sandha Perdhana; Tulus Sukreni; David Nurmanto (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
One of the important factors in a business is human resources. The quality of qualified human resources is able to make small industries successful. For the glorious economy of a small industry, it can be a better economy for a country. Therefore, small and medium enterprises need to be developed, one of which is in terms of human resources. Phenomena that occur in general in a small industry related to human resources include the lack of mastery of information technology. The use of the right technology has a relationship with the development of UMKM that have good competitiveness in the industrial era 4.0. This phenomenon is also experienced in one of the home industry in the South Tambun area which is used as a partner. From the results of the observations made, there are problems experienced by partners, including the distribution of limited production and marketing that is carried out conventionally by relying on word to mouth techniques. The stages of this service activity start from counseling, mentoring and mentoring. The briefing of the material presented was the process of managing the marketplace using Tokopedia and the process of designing logos and labels using Canva. From the evaluation of activities, it showed a percentage of pre-test values of 37% and post-test scores of 93. Then for evaluation related to the implementation of activities regarding enthusiasm and satisfaction of activities reached 92%.